The Roots of Cooperation - Zvonimir Bašic; Parampreet Christopher Bindra; Daniela Glätzle-Rützler; Angelo Romano; Matthias Sutter; Claudia Zoller (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the development of cooperation in 929 young children, aged 3 to 6. In a unified experimental framework, we examine pre-registered hypotheses about which of three fundamental pillars of human cooperation – direct and indirect reciprocity, and third-party punishment – emerges earliest as a means to increase cooperation in a repeated prisoner's dilemma game. We find that third-party punishment doubles cooperation rates in comparison to a control condition. Children also reciprocate others' behavior, yet direct and indirect reciprocity do not increase overall cooperation rates. We also examine the influence of children's cognitive skills and parents' socioeconomic background on cooperation.
Keywords: C91; C93; D01; D91; H41; 330; cooperation; reciprocity; third-party punishment; reputation; children; parents; cognitive abilities; socioeconomic status; prisoner's dilemma game; experiment